Russian Insurance Market: Federal, Regional Measures and Self-Regulation - ODINOKOVA, Tatjana (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).20, 2019)
Self-regulation has a long history of application and is an efficient mechanism for monitoring the activities of business entities, while it is a new element of financial regulation for Russia. The impact of the industry specifics of Russian insurance market is analyzed herein. The research gap covered by this work consists in the insufficient elaboration and validity of corporate regulation (self-regulation) of insurance market. The purpose of the article is to develop recommendations for minimization of the negative effects of the transition from state regulation to self-regulation of the insurance market. Analytical and statistical methods are used to determine the readiness of the insurance market and the efficiency of the measures implemented by the state for the transition from state regulation to self-regulation. Recommendations for minimization of the negative effects of the transition from state regulation to self-regulation are given by the author, namely: to single out the Life Insurers Association (LIA) and to increase its role in the regulation; to amend current legislation, taking into account territorial location and contribution to the development of the national insurance market, namely the division of the insurance companies into federal and regional ones and the implementation of the measures on the regulation.